Dipeptidyl peptidase 4 inhibitor improves brain insulin sensitivity, but fails to prevent cognitive impairment in orchiectomy obese rats - Hiranya Pintana (2018)
© 2015 Society for Endocrinology. It is unclear whether the dipeptidyl peptidase 4 (DPP4) inhibitor can counteract brain insulin resistance, brain mitochondrial dysfunction, impairment of hippocampal synaptic plasticity and cognitive decline in testosterone-deprived obese rats. We hypothesized that DPP4 inhibitor vildagliptin improves cognitive function in testosterone-deprived obese rats by restoring brain insulin sensitivity, brain mitochondrial function and hippocampal synaptic plasticity. Thirty male Wistar rats received either a sham-operated (S, nZ6) or bilateral orchiectomy (ORX, nZ24). ORX rats were divided into two groups and fed with either a normal diet (ND (NDO)) or a high-fat diet (HFO) for 12 weeks. Then, ORX rats in each dietary group were divided into two subgroups (nZ6/subgroup) to receive either a vehicle or vildagliptin (3 mg/kg per day, p.o.) for 4 weeks. After treatment, cognitive function, metabolic parameters, brain insulin sensitivity, hippocampal synaptic plasticity and brain mitochondrial function were determined in each rat. We found that HFO rats exhibited peripheral and brain insulin resistance, brain mitochondrial dysfunction, impaired hippocampal synaptic plasticity and cognitive decline. NDO rats did not develop peripheral and brain insulin resistance. However, impaired hippocampal synaptic plasticity and cognitive decline occurred. Vildagliptin significantly improved peripheral insulin sensitivity, restored brain insulin sensitivity and decreased brain mitochondrial reactive oxygen species production in HFO rats. However, vildagliptin did not restore hippocampal synaptic plasticity and cognitive function in both NDO and HFO rats. These findings suggest that vildagliptin could not counteract the impairment of hippocampal synaptic plasticity and cognitive decline in testosterone-deprived subjects, despite its effects on improved peripheral and brain insulin sensitivity as well as brain mitochondrial function.